Respiratory Syncytial Virus Vaccination During Pregnancy and Effects in Infants. Issue 1 (January 2021) - Madhi, Shabir A.; Polack, Fernando P.; Piedra, Pedro A.; Munoz, Flor M.; Trenholme, Adrian A.; Simões, Eric A. F.; Swamy, Geeta K.; Agrawal, Sapeckshita; Ahmed, Khatija; August, Allison; Baqui, Abdullah H.; Calvert, Anna; et al.
Abstract : (Abstracted from N Engl J Med 2020;383:426–439) Respiratory syncytial virus (RSV) is a leading cause of hospitalizations of infants with lower respiratory tract infections. In 2015, approximately 3.2 million children younger than 5 years were hospitalized because of RSV-associated lower respiratory infection, and 118, 000 died in hospital.